Pengaruh Mekanisme Corporate Governance terhadap Kualitas Laba - Siallagan, Hamonangan (Jurnal Widya Manajemen & Akuntansi, 2007)
The purpose of this research is to investigate and give empirical evidence of the effect of corporate governance mechanisms on earnings quality. The proposed hypotheses are as follows, (1) managerial ownership is positively influence earnings quality, (3) the proportion of independent board of commissioner positively influence earnings quality, (3) the existence of audit committee positively influence earnings quality. By using 74 samples and 197 observations, the result indicates that corporate governance mechanism effect earnings quality. The earnings quality of proxy stated by Sloan (1996), Chan et al (2001) and Warfield et al (1995) is discretionary accruals. The corporate governance mechanism has the ffict on earnings quality are: managerial ownership positively and statistically significant effect earnings quality, the proportion of board of commissioner negatively and statistically significant influence earnings quality, the existence of audit committee positively and statistically significant influence earnings quality.